Survey of Future Internet of Thing - Hani Purwati Hanifah (ITEJ (Information Technology Engineering Journals), 2020)
The Internet of Things is a technology that will become an integral part of human life. At present, its use has begun to be widely applied in various scientific fields such as agriculture, health, industry, etc. so that it has a very good impact. In addition, the development of this device has also reached a point where collaboration with various scientific fields has occurred. However, in addition to the benefits offered by the Internet of Things, there are challenges such as the use of energy in data transfer, memory limitations and so on as well as threats that can arise such as loss of privacy, leakage of data and information, or use to commit crimes in the physical world.